2015
DOI: 10.1038/srep08811
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism for Small Heat Shock Proteins to Function as Molecular Chaperones

Abstract: Small heat shock proteins (sHSPs) are molecular chaperones ubiquitously present in all forms of life, but their function mechanisms remain controversial. Here we show by cryo-electron microscopy and single particle 3D reconstruction that, at the low temperatures (4–25°C), CeHSP17 (a sHSP from Caenorhabditis elegans) exists as a 24-subunit spherical oligomer with tetrahedral symmetry. Our studies demonstrate that CeHSP17 forms large sheet-like super-molecular assemblies (SMAs) at the high temperatures (45–60°C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
39
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 50 publications
11
39
2
Order By: Relevance
“…Upon biotin binding, the avidins gain stability as indicated by their increased Tm values (Table ), which enable and presumably favour the dissociation into dimers. Other studies have indicated an enhanced activity upon dissociation of oligomers , demonstrating a common phenomenon of oligomer dynamics. In certain cases, the congregation of proteins results in additional functions , which have yet to be revealed for afifavidin and hoefavidin.…”
Section: Discussionmentioning
confidence: 79%
“…Upon biotin binding, the avidins gain stability as indicated by their increased Tm values (Table ), which enable and presumably favour the dissociation into dimers. Other studies have indicated an enhanced activity upon dissociation of oligomers , demonstrating a common phenomenon of oligomer dynamics. In certain cases, the congregation of proteins results in additional functions , which have yet to be revealed for afifavidin and hoefavidin.…”
Section: Discussionmentioning
confidence: 79%
“…However, relatively little known information is available about CeHSP17 molecular function and properties in C. elegans (Candido, 2002). Recently, we have reported our findings on the ability of CeHSP17 protein to enable growth of Escherichia coli cells at a lethal temperature of 508C (Ezemaduka et al, 2014) and mechanistically show that CeHSP17 protein could exhibit chaperone-like activity in preventing the stress-induced aggregation of model substrate proteins through the formation of super-molecular assemblies (Zhang et al, 2015). Despite these findings, we are still challenged with what CeHSP17 protein does as a molecular chaperone in C. elegans.…”
mentioning
confidence: 70%
“…Heat shock proteins (Hsp) comprise a certain group of highly conserved stress proteins which attracted attention due their overexpression in cancer tissues12. Overexpression of these proteins is related to metastatic potential, resistance to chemotherapy and poor prognosis3.…”
mentioning
confidence: 99%